Effect of ionizing radiation on properties of restorative materials. Issue 2 (February 2018) - Brandeburski, Suzane Boa Nova; Della Bona, Alvaro
Abstract: Objective: To evaluate the effect of ionizing radiation from high energy X-ray on properties of restorative materials. Methods: Study materials (3M-ESPE) were: Z250—microhybrid resin-based composite (Filtek Z-250); Z350—nanofilled resin-based composite (Filtek Z-350XT); VIT—resin-modified glass ionomer cement (Vitremer); and KME—conventional glass ionomer cement (Ketac Molar Easymix). Sixty bar-shaped and cylinder-shaped specimens were fabricated from each material. Specimens were light activated (980 mW/cm 2, Radii, SDI) for 60 s (3 × 20 s for Z250 and Z350) and 120 s (3 × 40 s for VIT) and thirty specimens from each shape were irradiated (IR) with 1.8 Gy/day for 39 days (total IR = 70.2 Gy). IR and non-irradiated (NI) specimens were evaluated for flexural strength ( σ, n = 30) followed by fractography (SEM), diametral tensile strength (DTS, n = 30), hardness (H, n = 10), surface roughness (Ra, n = 10) and chemical composition (n = 3). The IR effect on each material property was statistically analyzed using Student's t test ( α  = 0.05). Data from σ and DTS were also analyzed using Weibull statistics. Results: IR significantly increased the mean σ values of VIT and KME and the mean DTS value of VIT (p < 0.05). IR increased Ra and H values for VIT and decreased H value for Z-250 (p < 0.05). The remaining materials and properties were not significantly affected by IR (p > 0.05). There was no significant change on materials composition after IR. Significance: The recommended radiotherapy protocol for head and neck cancer altered some material properties, mainly for glass ionomer cements. Such variations on material properties are not related to chemical composition changes.